Strategies for optimizing the use of local electronic catalogs in the procurement process - Pawe, Dominika Odelberta Gaudenzia; Utami, Intiyas; Man, Stanis (Jurnal Ekonomi dan Bisnis, 2024)
The government uses the e-purchasing method through local electronic catalogs (KEL) to support their operational expenditure by focusing on domestic products provided by MSEs and cooperation. This research aims to describe the use of KEL in the procurement process within the regional government of NTT. A descriptive qualitative method was used in this research, with observation, documentation, and interview as the data collection methods. This study found that the regional government apparatus, as the main user of the e-catalog platform, is not yet familiar with procurement planning. In contrast, they could benefit from understanding how to use the e-purchasing system. Further, the supporting factors for KEL are support from procurement parties, the availability of competitive prices and qualities of products, and a well-regulated policy. In comparison, the obstructing factors are lack of knowledge and consistency of the government apparatus on the policy about using KEL, limited alternatives of competitive prices and qualities of available products, and lack of accountability in an e-purchasing mechanism. Therefore, an optimization strategy of well-integrated socialization and formation on using KEL is needed, along with a scheduled evaluation and monitoring by internal auditors and an increasing range of available products on current providers.